2007
DOI: 10.1038/sj.leu.2405001
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-142 by proto-oncogene LMO2 and its co-factors

Abstract: previously described BCL6/IG translocations with a breakpoint in the 5 0 UTR of BCL6, or in the distant ABR. 2,6 Thus, in our cases BCL6 deregulation can not be explained by promoter substitution. In case no. 2 the inactivation of BCL6 negative autoregulation sites by mutations can be hypothesized, but in case no.1, for which no mutation was found inside these regions, the most reliable hypothesis involves cis-acting elements provided by the partner sequences. The expression of TMEM75, the closest locus broug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…15 Of considerable interest given its own regulation by an miRNA, LMO2 was recently implicated in down-regulating miRNA-142. 16 In summary, recent studies, including the one reported by Felli et al 10 , have shown that LMO2 is regulated at both a posttranscriptional and post-translational level in erythroid progenitors. This undoubtedly contributes to the precision with which erythrocyte production is controlled in vivo.…”
mentioning
confidence: 77%
“…15 Of considerable interest given its own regulation by an miRNA, LMO2 was recently implicated in down-regulating miRNA-142. 16 In summary, recent studies, including the one reported by Felli et al 10 , have shown that LMO2 is regulated at both a posttranscriptional and post-translational level in erythroid progenitors. This undoubtedly contributes to the precision with which erythrocyte production is controlled in vivo.…”
mentioning
confidence: 77%
“…To date, very few miRNAs have been shown to play important roles in HSC development in vertebrates in vivo. miR-142-3p is specifically expressed in HSCs (AGM and CHT) and T cells (thymus) in zebrafish, mouse and other species [15][16][17][18][19][20][21]. By knockdown of miR-142a-3p using 2 specific MOs, the numbers of HSCs and T cells were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-144 and miR-451, as direct targets of the critical hematopoietic master regulator GATA1, are required for erythropoiesis in zebrafish and mouse [11][12][13]. miR-142-3p is an evolutionally conserved miRNA of vertebrates, which is expressed in many different hematopoietic cells [14][15][16][17][18][19][20][21]. Chen et al [15] first reported that miR-142 is expressed in embryonic and adult hematopoietic tissues, including the fetal liver, bone marrow, spleen and thymus, in mice, indicating its role in both embryonic and adult hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the primary transcript of miR-142 is about 750 bp in length, and that there are no introns in this gene. In our previous study, it was demonstrated that LMO2 could negatively regulate the expression of miR-142 by binding to a typical LMO2 binding site located in the upstream region of the miR-142 locus [39]. In addition, the TESS online transcription element search system (http:// www.cbil.upenn.edu) revealed that there are two typical CEBP-β sites in the 2 kb promoter region, as indicated in Figure 2D.…”
Section: Introductionmentioning
confidence: 88%